Pilot study comparing effects of infrared neuromodulation and transcranial magnetic stimulation using magnetic resonance imaging - Bibb, Sophia A.; Yu, Emily J.; Molloy, M. Fiona; LaRocco, John; Resnick, Patricia; Reeves, Kevin; Phan, K. Luan; Krishna, Sanjay; Saygin, Zeynep M. (Frontiers in Human Neuroscience, 2025)
No prior work has directly compared the impacts of transcranial photobiomodulation (tPBM) and transcranial magnetic stimulation (TMS) on the human brain. This within-subjects pilot study compares the effects of tPBM and TMS of human somatomotor cortex on brain structural and functional connectivity. Eight healthy participants underwent four lab visits each, each visit consisting of a pre-stimulation MRI, stimulation or sham, and a post-stimulation MRI, respectively. Stimulation and sham sessions were counterbalanced across subjects. Collected measures included structural MRI data, functional MRI data from a finger-tapping task, resting state functional connectivity, and structural connectivity. Analyses indicated increased activation of the left somatomotor region during a right-hand finger-tapping task following both tPBM and TMS. Additionally, trending increases in left-lateralized functional and structural connectivity from M1 to thalamus were observed after tPBM, but not TMS. Thus, tPBM may be superior to TMS at inducing changes in connected nodes in the somatomotor cortex, although further research is warranted to explore the potential therapeutic benefits and clinical utility of tPBM.